Estudio fluviomorfológico del río San Agustín en el sitio Vega Rivera cantón Santa Rosa provincia de El Oro y su incidencia en el libre aprovechamiento de materiales pétreos. - Matamoros Condoy, Henry Alejandro (2015)
Mining concessions and free use of stone materials, it causes unfavorable change in the hydraulic conditions of the runway at San Agustin River Site Vega Rivera, so the present work aims to make the Fluviomorfológico study evaluating the conditions for free use of stone materials in San Agustin Rivera Vega river site.      For which it has made a complete survey of the area where is located the quarry San Agustin belonging to the Autonomous Provincial Council of El Oro, a morphological analysis was also performed to determine the sections and shape of the riverbed, was also carried out a full hydrological study of the watershed of the river where it was determined the area, perimeter, shape, elevation, average elevation, drainage density, slope of the main channel and flows for a while given return, also a hydraulic study which has determined the current flows, and integration of all information in a computer application designed for this purpose (HEC-RAS), where a modeling of possible flooding areas was made, entering return flows obtained.      The results of this study, had the effect of increasing levels of water for periods calculated return, by which it is proposed encausar river using walls 2.50 m in height and a bottom width of 55 m, to avoid possible flooding, and thus also get a good sedimentation, and achieves a better extraction of the material, and mitigate damage.